2021
DOI: 10.1038/s12276-021-00682-z
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 receptor-2 contributes to KRAS-driven lung tumor formation by promoting interleukin-6-mediated inflammation

Abstract: Although lung cancer is the leading cause of cancer-related deaths worldwide and KRAS is the most frequently mutated oncogene in lung cancer cases, the mechanism by which KRAS mutation drives lung cancer has not been fully elucidated. Here, we report that the expression levels of leukotriene B4 receptor-2 (BLT2) and its ligand-producing enzymes (5-LOX, 12-LOX) were highly increased by mutant KRAS and that BLT2 or 5-/12-LOX blockade attenuated KRAS-driven lung cell proliferation and production of interleukin-6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…In recent years, many studies have demonstrated that immune function, inflammation, and tumor occurrence are closely related. For instance, immune-related factors can affect the tumor microenvironment and promote tumorigenesis ( 11 , 12 ). Based on preoperative blood values detected by standard laboratory tests, preoperative immune indicators, including LMR, PLR, and NLR, are used because they can predict the presence of malignant tumors, such as lung cancer and prostate cancer, and predict the survival of patients ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have demonstrated that immune function, inflammation, and tumor occurrence are closely related. For instance, immune-related factors can affect the tumor microenvironment and promote tumorigenesis ( 11 , 12 ). Based on preoperative blood values detected by standard laboratory tests, preoperative immune indicators, including LMR, PLR, and NLR, are used because they can predict the presence of malignant tumors, such as lung cancer and prostate cancer, and predict the survival of patients ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…By binding to its receptor BLT 2 , LTB 4 stimulates IL-8 production and promotes metastasis of breast cancer cells in concert with NF-KB (20). Lipids catalyzed by 5-LO and 12-LO also promotes lung tumor cell proliferation and the production of IL-6, another important in ammatory mediator of the TME (21). Our results have rst provided preliminary evidence that leukotriene B4 promotes glioma.…”
Section: Discussionmentioning
confidence: 54%
“…Leukotriene B4 receptor 2 (LTB4R2), a g-protein-coupled receptor regulates chemotaxis and wound healing. Its expression has been associated with invasion and metastasis of lung cancer and breast cancer [15] [16]. It was also confirmed that high expression of LTB4R2 promoted CRC cell proliferation [17].…”
Section: Discussionmentioning
confidence: 74%